MEDIA MADANIYAT ASARLARINI TAHLIL QILISHNING USLUBIY ASOSLARI (Multidisciplinary Journal of Science and Technology, 2025)
This article aims to improve the critical thinking of future specialists for using media education. To teach future teachers the right perception, critical analysis and evaluation of the analysis of works of media culture, and also to influence the importance of research on the impact of mass media on people and the education of the younger generation. has been read.